THE ROLE OF CENTRAL ASIA IN WORLD HISTORY IN THE MIDDLE AGES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Nowadays, when someone hears about Central Asia, they immediately think about 5 independent countries that have no access to the sea, their problems, etc. After reading this article, you will understand that the role of this region was colossal. Precisely, in the vast expanses of the steppes, countless caravans passed through the deserts, and huge states arose on their territory that amazed people with their wealth and size.
Keywords: Great Silk Road; Samarkand; Bukhara; silk; trade; culture; science; art; Turks; Mongols